2017
DOI: 10.5114/hivar.2017.68117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV risk factors on survival in Iranian HIV-infected patients: A Bayesian approach to retrospective cohort

Abstract: Introduction: Human immunodeficiency virus (HIV) infection is recognized as a human health issue, and its social, cultural, economic, and political consequences lead to an extremely large problem for human health. The aim of this study is to evaluate association between risk factors and HIV-positive patient's survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
(31 reference statements)
2
9
0
1
Order By: Relevance
“…The results also showed that sexual transmission of HIV is signi cantly associated with the survival of HIV infected patients. This nding is consistent with other studies that conducted by Maracy et al in Iran [27].…”
Section: Resultssupporting
confidence: 93%
“…The results also showed that sexual transmission of HIV is signi cantly associated with the survival of HIV infected patients. This nding is consistent with other studies that conducted by Maracy et al in Iran [27].…”
Section: Resultssupporting
confidence: 93%
“…Alternatively, viruses that contribute to a persistent infection, including HIV, HCV, and HBV, have developed multiple strategies to subvert or evade the immune responses. The mechanisms for this immune‐escape strategy have still to be fully understood . It has been shown that miR‐146a regulates the production of inflammatory cytokines by targeting IRAK1.…”
Section: Mir‐146a In Hbv/hcvmentioning
confidence: 99%
“…The mechanisms for this immune-escape strategy have still to be fully understood. [41][42][43][44] It has been shown that miR-146a regulates the production of inflammatory cytokines by targeting IRAK1. Forkhead-box transcription factors (FOXP3), which is known as specific Treg cells marker and controls the function and development of Treg cells.…”
Section: Mir-146amentioning
confidence: 99%
“…B19V infection and the consequent anemia are considered serious issues in HIV patients. A proportion of patients are cured by blood transfusions and high-dose intravenous immunoglobulin (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%